Upaya Meningkatkan Hasil Belajar Peserta Didik Pada Materi Gejalan Yang Terjadi Di Atmosfer Dan Hidrosfer Melalui Model Make A Match Di Kelas VII.E SMP Negeri 1 Jonggol Kabupaten Bogor Tahun Pelajaran 2015/2016 - Agung Mahmilasari (JURNAL KAJIAN ISLAM MODERN, 2021)
One of the low learning outcomes of students is because teachers still use conventional learning models. The make a match learning model is proven to be able to improve student learning outcomes on the material phenomena that occur in the atmosphere and hydrosphere in class VII-E of SMP Negeri 1 Jonggol. The results of the study can be concluded that there is an increase in learning outcomes through test and non-test instruments. Data analysis of class success with a range of 7.10 - 10.00 in cycle 1 was 102 and cycle 2 was 140. The average score in cycle 1 was 0.64 and cycle 2 was 0.88, there was an increase of 0.24. The majority of students in cycle 1 on the distribution of values ​​75-87 and cycle 2 on the value of 88-100. Students who reach or exceed the KKM in cycle 1 are 25 students in cycle 2 are 37 students. The percentage that reaches the KKM in cycle 1 is 0.62 and in cycle 2 is 0.92. There is an increase of 0.30. Attention of students when starting learning in cycle 1 is 60% and in cycle 2 is 93.3% there is an increase of 33.3%. Student response in learning in cycle 1 is 76.5% and in cycle 2 is 96.9% there is an increase by 20.4%. The seriousness of students in solving problems in cycle 1 is 66.7% and in cycle 2 is 80% there is an increase of 13.3%. The courage of students in appearing in front of the class to answer the questions given by the teacher in cycle 1 is 65% and in cycle 2 is 85%, there is an increase of 20%. The seriousness and ability of students to ask questions about the symptoms of the hydrosphere and their impact on life in cycle 1 was 73.3% and in cycle 2 was 93.3% an increase of 20%.